Synergic Neuroprotection Between Ligusticum Chuanxiong Hort and Borneol Against Ischemic Stroke by Neurogenesis via Modulating Reactive Astrogliosis and Maintaining the Blood–Brain Barrier - Yu, Bin; Yao, Yao; Zhang, Xiaofeng; Ruan, Ming; Zhang, Zhennian; Xu, Li; Liang, Tao; Lu, Jinfu (Frontiers in Pharmacology, 2021)
Background: Ligusticum chuanxiong Hort. (LCH) is a famous ethnomedicine in Asia for its excellent output on stroke treatment, and borneol usually acts as an assistant for its reducing permeability of blood–brain barrier (BBB) after stroke. Although their synergy against brain ischemia was verified in previous studies, the potential mechanism is still unknown. Methods: The research aimed to explore the exact synergic mechanisms between LCH and borneol on neurogenesis within the areas of dentate gyrus and subventricular zone. After treating middle cerebral artery occlusion rats with LCH (0.1g/kg) and/or borneol (0.08 g/kg), neurological severity score, brain infarct ratio, Nissl staining, Evans blue permeability, BBB ultrastructure, and expressions of von Willebrand factor and tight junctions associated proteins were measured. Colocalizations of Nestin+/BrdU+ and doublecortin+/BrdU+, and expressions of neuronal nuclei (NeuN) and glial fibrillary acidic protein (GFAP) were observed under a fluorescence microscope. Moreover, astrocytes polarization markers of complement component 3 and pentraxin 3, and relevant neurotrophins were also detected by immunoblotting. Results: Basically, LCH and borneol had different focuses, although both of them decreased infarct areas, and increased quantity of Nissl bodies and expression of brain–derived neurotrophic factor. LCH increased neurological severity score, NeuN+ cells and the ratios of Nestin+/BrdU+ and doublecortin+/BrdU+, and decreased GFAP+ cells and ciliary neurotrophic factor expression. Additionally, it regulated the expressions of complement component 3 and pentraxin 3 to transform astrocyte phenotypes. Borneol improved BBB ultrastructure and increased the expressions of von Willebrand factor, tight junctions associated proteins, vascular endothelial growth factor and vascular endothelial growth factor receptor 2. Unexpectedly, their combined therapy showed more obvious regulations on Nissl score, Evans blue permeability, doublecortin+/BrdU+, NeuN+ cells, brain–derived neurotrophic factor and vascular endothelial growth factor than both of their monotherapies. Conclusion: The results indicated that LCH and borneol were complementary to each other in attenuating brain ischemia by and large. LCH mainly promoted neural stem cells proliferation, neurogenesis, and mature neurons preservation, which was probably related to the transformation of reactive astrocytes from A1 subtype to A2. While borneol preferred to maintain the integrity of BBB, which provided neurogenesis with a homeostatic environment.